CORROSION RESISTANCE OF SELF-COMPACTING CONCRETE CONTAINING CALCIUM STEARATE - AGUS MARYOTO; BUNTARA STHENLY GAN; NOR INTANG SETYO HERMANTO; RACHMAD SETIJADI (Journal of Engineering Science and Technology, 2018)
This study aims to determine the corrosion resistance of self-compacting concrete (SCC) combined with calcium stearate (CS), Ca(C18H35O2)2. The concrete qualities tested are 20, 30, and 40 MPa. The CS dose used ranges from 0 to 2.85% of the cement weight. Two types of testing were performed in this study, namely compressive strength and accelerated corrosion tests. The compressive test was performed using cylinders 150 mm in diameter and 300 mm in height and accelerated corrosion specimen was a prism 100 x 100 x 200 mm. The results show the improvements of the compressive strength of SCC 20, 30 and 40 MPa without and with CS are 28, 31, 28, and 37%; 16, 8, 10 and 3%; and 20, 14, 6 and -2% respectively, compared with conventional concrete. The corrosion attack decreased by around 29, 46, 86 and 86% for SCC 20 MPa with CS content of 0, 0.28, 2.43, and 2.85% respectively; 23, 27, 34, and 65% for SCC 30 MPa with CS content of 0, 0.24, 1.20 and 2.40% respectively; and around 7, 46, 62 and 63% for SCC 40 MPa with CS content of 0, 0.19, 0.93, and 1.86% respectively compared with conventional concrete